Detection of dioxin-induced demethylation of mouse Cyp1a1 gene promoter by a new labeling method for short DNA fragments possessing 5'-methylcytosine at the end - Hisaka Kurita; Toshiki Aiba; Toshiyuki Saito; Seiichiroh Ohsako (Genes and Environment, 2018)
Abstract Environmental factors stimulate alteration of DNA methylation level. Investigation of the genome-wide DNA methylation status is important for environmental health studies. We here designed a genomic DNA amplification and labeling protocol using a methylation-sensitive restriction enzyme HinP1 I. This method can specifically amplify genomic DNA fragments possessing methyl-CpG at the end. The fragments are a relatively short size and dominantly located on CpG-islands. By using the samples prepared by this method, a dioxin-induced change in the methylation level of the mouse Cyp1a1 promoter was successfully evaluated using oligonucleotide probes covalently bound onto a glass plate. The method developed in this paper would be useful for other genome-wide analysis platforms for the large scale epigenome-wide association studies (EWAS) including human epidemiological samples.